Kajian Teologi Tentang Doa Dalam Kitab Mazmur Dan Implementasinya Bagi Orang Percaya Pada Masa Kini - Ilenus Penggu; Sabda Budiman (DA'AT : Jurnal Teologi Kristen, 2024)
Prayer becomes a very central part of the believer's life. Not only today, but throughout the history of the life of the faithful, prayer has become an important spiritual part of the faith. So did a biblical figure named David. David's prayers can be investigated in the book of Psalms. The book of Psalms is a book of verses that presents david's real prayer life experience. David's prayer life is an example for believers today. Therefore, the author wants to examine the theology of prayer in the tips of the Psalms and their application to today's believers. To study and explore this topic, the author uses a quality research method with a descriptive approach. The author finds that there are at least 3 types of prayers in the book of Psalms, namely prayers of supplication, prayers of thanksgiving, and prayers of belief. The application that believers can make from the study of prayer in the Psalms is prayer as a personal relationship with God, prayer as an act of faith, and prayer as worship. All prayers begin with a special relationship between God and man. Doa menjadi bagian yang sangat sentral dalam kehidupan orang percaya. Tidak hanya saat ini saja, tetapi sepanjang sejarah kehidupan orang beriman, doa telah menjadi bagian spiritual iman yang penting. Begitu pula seorang tokoh Alkitab yang bernama Daud. Doa-doa Daud dapat diselidiki di dalam kitab Mazmur. Kitab Mazmur merupakan kitab syair yang menyajikan pengalaman kehidupan doa yang nyata dari Daud. Kehidupan doa Daud menjadi teladan bagi orang percaya saat ini. Oleh karena itu, penulis hendak meneliti teologi doa dalam kiatb Mazmur dan penerapannya bagi orang percaya masa kini. Untuk mengkaji dan mendalami topik ini, penulis menggunakan metode penelitian kualitiatif dengan pendekatan deskriptif. Penulis menemukan setidaknya ada 3 jenis doa dalam kitab Mazmur yaitu doa permohonan, doa ucapan syukur, dan doa kepercayaan. Penerapan yang dapat dilakukan oleh orang percaya dari pengkajian doa dalam Mazmur yaitu doa sebagai hubungan relasi pribadi dengan Allah, doa sebagai tindakan iman, dan doa sebagai ibadah. Semua doa itu diawali dengan suatu hubungan khusus antara Allah dan manusia.